Socioclinical profile of children with asthma in Al-Majmaah Health Province - Al-Ghamdy, Yasser S.; Al-Haddad, Nasir S.; Adelgadir, Muzamil H.; Qureshi, Naseem A.; Saleh, Mahmood A.; Khalil, Mohamed M. (Saudi Medical Journal, 2000)
OBJECTIVE: Although asthma in children constitutes a major health problem, there is a dearth of literature on different aspects of asthma in rapidly developing countries. This cross-sectional research aims to study the socioclinical profile of asthmatic children and the impact of asthma symptoms on their life style.METHODS: The sample of this study, drawn from pediatric clinics of a general hospital and primary health care centers during a period of six months, comprised of children under 13 years of age who met the operational diagnostic criteria for asthma. The data collected from multiple sources on a semistructured questionnaire was analyzed by using different statistical tests.RESULTS: The results showed that male children represented 69% of the sample and children under one year of age manifested significantly severe degree of asthma. The frequency of asthma symptoms decreased in most of the studied children with increasing age. Further, they have insignificant family history of asthma (48.5%) but a significant smoking at home in severely affected children (59%). Moreover, most of them (88%) were mainly characterized by a combination of asthmatic symptoms of variable severity that adversely affected their sleep pattern and significantly resulted in school absences and increased days stay in hospital.CONCLUSION: The revealed socioclinical profile of studied children with asthma has adverse impact on certain components of their life style, which shows the need for re-activating relevant treatment modalities including health education and changing certain habits like parental smoking at home, which adversely affects asthma.